South China Sea Seeps - Chen, Duofu; Feng, Dong (Springer Singapore Pte. Limited, 2023)
This open access book presents an overview on seep systems in South China Sea. It includes numerous illustrations and photographs of the seeps that never seen before. It also introduces multidisciplinary research results to stimulate further research interest.
Keywords: Google Library Project; Electronic books